Study of physico-chemical properties of raw materials for solid propellant - Viktor Muratov; Sergey Borisenko; Nikolay Koshevoy; Anatoliy Sanin; Maxim Kravchenko (Авіаційно-космічна техніка та технологія, 2022)
In the study of the physicochemical properties of low molecular weight polybutadiene rubber with functional hydroxyl groups (Hydroxyl Terminated Poly Butadien – HTPB), which is a raw material for solid rocket fuel (SRP), an experimental batch of rubber was made and 3 synthesis of experimental batches of low molecular weight polybutadiene rubber with functional hydroxyl groups was carried out. The current work obtains a HTPB physical and chemical characteristics that meet the requirements of regulatory documentation (ND). During this work, the physical and chemical characteristics of HTPB rubber were determined to compliance with regulatory documentation. The readiness of the equipment for conducting the synthesis of HTPB rubber (collector, dispensers, reactor, separator, rotary evaporators, vessel, igniter) was checked. The sequence of execution of technological operations for the synthesis of rubber has been worked out. According to the results of the study, the compliance of the physical and chemical parameters of the obtained raw materials for SPR with the requirements of the ND was established and a conclusion was made about the admission to production. After checking the operability of the main and auxiliary technological equipment, no comments were found. Because of the preparation of technological equipment for the synthesis of HTPB rubber, no comments were found. According to the results of the operations of loading samples into the dispensers and collector, it was found that with a decrease in the volume of butadiene in the container, it is necessary to increase the argon pressure to load it into the collector. According to the results of the operations, filling the reactor with prepared samples of raw materials, no comments were found either. The results of the study of the physicochemical properties of the obtained raw materials for the manufacture of SPR showed almost complete compliance with the requirements of ND, except for the weight loss during drying. Subsequent studies are aimed at modifying the technology for obtaining low molecular weight polybutadiene rubber and studying the physicochemical properties of raw materials for solid rocket fuel.